On rate-variable multidimensional DS - Nan Guo (IEEE Journal on selected areas in communications)
A general model for M-ary direct sequence-spread spectrum (DS/SS) communications is presented to provide multiple services in direct sequence-spread spectrum multiple access (DS/SSMA). The main idea is to allow each user to use parallel orthogonal spreading sequences, depending upon its needs. More specifically, each service level is associated with certain combinations of the sequences. We use a code, which we refer to as a ?mapping code?, to form a multidimensional signal constellation. Thus, the data rate can be changed by changing the mapping code. Further, techniques of sequence sharing (reuse) and sequence arrangement (allocation), suitable for packet switching, are proposed; this allows support of multimedia services, while resulting in a reduction of sequence consumption. We evaluate error rates in the presence of multiple access interference (MAI) and additive white Gaussian noise (AWGN). Numerical results are given to show the effects of the system configuration, the data rates, and other system performance measures